Previous studies related to the use of sciences technology in the learning of special education needs pupils with visual impairment - Ismail, Muhd Zulkifli; Nordin, Mohd Norazmi; Mohd Isa, Nor Aainaa; Baharudin, Siti Mastura; Abbas, Mohd Saleh; Muhd Feisal Ismail, Albert Feisal; Maidin, Siti Sarah (African Science Publications, 2024)
In Malaysia, Special Education has started since the early 1920s when a group of volunteers opened schools for students with visual and hearing disabilities. In 1978 a cabinet committee reviewed the Implementation of Education Policy through Certificate 169 which stated that there was an awareness of the government's responsibility towards the education of disabled children. The government is advised to take responsibility for providing education services to this group. While volunteers are also encouraged to be involved in advancing the education of disabled children. On June 30, 1981, the Education Planning Committee meeting decided to establish a committee to study the needs of their respective tasks towards these children. In 1996 the Special Education Act was gazetted. This Act emphasizes the role and law that drives special education programs in Malaysia. Through the free education act, inclusive class programs, the preparation of lesson plans and support from various parties are emphasized in the special education system in Malaysia.